Implementasi Peraturan Daerah Kabupaten Tulungagung Nomor 10 Tahun 2011 Tentang Penyelenggaraan Perparkiran Di Kabupaten Tulungagung - Aries Prasetyo; Teguh Pramono; Imam Fachruddin; Daimul Abror; Muhamad Chairul Basrun Umanailo (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
The Tulungagung Regency Government issued Regional Regulation Number 10 of 2011 concerning Parking Management as a juridical effort to deal with various problems related to parking. This regional regulation is used as a guideline for organizing parking on the side of public roads and special parking areas. The contents of this regional regulation regulate the administration of parking and parking fees in Tulungagung Regency so that it is hoped that the implementation of parking will be efficient and effective. The purpose of this study is to describe the implementation of the Tulungagung Regency Regional Regulation No. 10 of 2011 and to analyze the inhibiting factors for the implementation of the Regional Regulation. This study uses a qualitative research method based on the philosophy of postpositivism which is used to examine the condition of natural objects. Data collection techniques were carried out by observation, interviews, documentation, and triangulation. The results of the study found that the cause that hindered the implementation of this Regional Regulation was the lack of human resources (HR), where the number of employees was not proportional to the size of the work area. which makes the lack of supervision resulting in the practice of levies being carried out by parking attendants still ongoing.